Alignment of carbon nanotubes by dip pen naolithography - Low, Kay Boon. (2009)
Carbon nanotube has a range of applications ranging from ultra-small electronic and sensing devices to multifunctional materials. This research investigates the way to align carbon nanotube on the substrate to be used for microelectronics applications. Dip-Pen Nanolithography, which is a direct writing method to produce sub 100nm features with high resolution, was used to pattern the substrate. The hydrophobic end(S-end) of the 11- amino-1-undecanethiol (AUT) ink will form covalent bonds with gold whereas the hydrophilic ends (NH3) will be repelled from the gold. This will form a self assembly layer. In this research, the optimum gold thickness and ink concentration were determined to achieve the smallest AUT line width that can be written on the substrate. The carbon nanotube was attached to the hydrophilic end (NH3) of AUT ink. Modified Molecular combing was then used to align the carbon naotubes on the substrate. The result is an array of carbon nanotube with width 1-4nm aligned in the same direction on the silicon substrate coated with gold. This shows that it is possible to assemble carbon nanotube on the substrate to explore its applications in many applications.